Comparison of Saline Infusion Sonography with Hysterosalpingography for its Accuracy in Diagnosing Tubal Status in Subfertile Females - Salahuddin, Nohseen; Mumtaz, Ambreen; Iftikhar, Sanam; Siddique, Uzma; Sheikh, Mariam; Waheed, Alia (Journal of Fatima Jinnah Medical University, 2024)
Background: Subfertility is seen in approximately 10-15% of couples of reproductive ages. Tubal factors account for 25-35% of cases of subfertility. Commonly used tests for tubal patency are hysterosalpingography (HSG), laparoscopy and saline infusion sonohysterography (SIS). Saline infusion sonohysterography is a non-invasive test and used in many countries for checking tubal patency with promising results. This study was to compare saline infusion sonohysterography (SIS) with hysterosalpingography (HSG) in terms of diagnostic accuracy in determining tubal patency in subfertile females in a charity hospital. Patients and methods: A prospective cross-sectional study conducted in the Gynaecology Department, Akhter Saeed Trust Hospital, from 15.10.2017 to 14.10.2019. Non-probability consecutive sampling was done and women presented between 18-40 years of age, for evaluation of primary and secondary subfertility and trying to conceive for more than one year were included. Patients with active pelvic infection, active vaginal bleeding or husband having azoospermia were excluded. After informed consent SIS and HSG were done on same day to see the patency of tubes and any complication with both procedures. The data was analyzed SPSS version 23 was used for statistical analysis. Results: Total 166 patients underwent SIS and HSG simultaneously. SIS showed tubal patency in 106 (63.86%) patients and out of these patients, 96 were true positive and 10 were false positive. HSG confirmed tubal patency in 103 (62.05%) cases, out of which 7 patients (false negative) had no patency on SIS. The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of SIS with HSG in determining tubal patency of subfertile female was 93.20%, 84.13%, 90.57%, 88.33% and 89.76%, respectively. No patient had any serious complications with SIS. Conclusion: This study concluded that saline infusion sonography is a safe and effective tool with high diagnostic accuracy for determining the tubal patency in subfertile females.